RETRACTED: Comparison modern of turbulence models for the 2D NASA wall-mounted hump separated flow problem - Madaliev Murodil; Usmonov Mavlonbek; Umirzakov Zuhriddin; Usmonov Shukurillo; Ismoilov Muslimbek; Adilov Zarifjon; Alimova Nigora (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001